Comparing analytical and Monte-Carlo-based simulation methods for logic gates SET sensitivity evaluation. (November 2020) - Schvittz, R.B.; Aguiar, Y.Q.; Wrobel, F.; Autran, J.-L.; Rosa, L.S.; Butzen, P.F.
Abstract: This paper presents a discussion related to two different methods used to evaluate logic gate susceptibility considering Single Event Transient faults at the layout level. These methods can be adopted into radiation-hardening-driven optimizations to improve the overall reliability of circuits. The results show that the simulation approach presents a higher accuracy by considering charge-sharing effects. At the same time, the analytical method can provide similar results in a faster manner.